1998
DOI: 10.1007/s004670050448
|View full text |Cite
|
Sign up to set email alerts
|

Primary vesicoureteral reflux: review of current concepts

Abstract: The well-known association between vesicoureteral reflux and urinary tract infection is the basis for pathophysiological and therapeutic implications which have dominated the literature on the subject for the last 2 decades. We critically review the following issues: (1) does urinary tract infection cause reflux? (2) does reflux predispose to infection? (3) does reflux predispose to pyelonephritis? (4) does reflux predispose to a renal parenchymal scar? (5) does long-term urinary antibiotic prophylaxis prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 49 publications
1
34
1
6
Order By: Relevance
“…Some studies have questioned the efficacy of antibiotic prophylaxis in patients with recurrent UTI, 6,13 but to date, none have been conclusive. One meta-analysis review concluded that antibiotic prophylaxis "may not" prevent recurrent symptomatic UTI on children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have questioned the efficacy of antibiotic prophylaxis in patients with recurrent UTI, 6,13 but to date, none have been conclusive. One meta-analysis review concluded that antibiotic prophylaxis "may not" prevent recurrent symptomatic UTI on children.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Beyond VUR and GU anomalies, some other risk factors have been found associated with recurrent UTI. 5,6 The standard treatment for UTI infection in primary VUR patients is antibiotic prophylaxis. Since VUR is the most common abnormality in children with UTI, to prevent recurrences, antibiotic prophylaxis is started immediately after UTI treatment is finished and continued until a voiding cystourethrogram (VCUG) excludes VUR.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the notably conservative approach applied in group 2, this study reveals that the traditional concept of surgery as the therapy of choice to prevent kidney damage in patients with increased risk for unfavorable clinical course, high-grade VUR, and nephropathy at diagnosis [8][9][10][11] is, and still is for some health care professionals, the cause for the selection of surgery as the initial therapeutic option for these patients. It has been observed how, in spite of a trend towards conservative treatment in the pre-guideline era, patients with VUR IV-V and nephropathy at diagnosis tended to be excluded from the sequential treatment algorithm.…”
Section: Discussionmentioning
confidence: 82%
“…Reflux grading may still be considered relevant only whether lack of improvement or progression of VUR grade, in a patient otherwise asymptomatic, is considered an indication for surgery too. However, actual association among VUR degree, renal damage, and need for surgery remains controversial as well as the real need to treat persistent VUR [12,16]. Furthermore, with a routine use of PD-VUS, comparison would be done among multiple PD-VUSs, increasing consistency.…”
Section: Discussionmentioning
confidence: 99%